3D-Printed Synthetic Vocal Fold Models - Romero, Ryan G. T. (J Voice, 2020)
OBJECTIVE: Synthetic vocal fold (VF) models used for studying the physics of voice production are comprised of silicone and fabricated using traditional casting processes. The purpose of this study was to develop and demonstrate a new method of creating synthetic VF models through 3D printing in order to reduce model fabrication time, increase yield, and lay the foundation for future models with more lifelike geometric, material, and vibratory properties. STUDY DESIGN: Basic science METHODS: A 3D printing technique based on embedding a UV-curable liquid silicone into a gel-like medium was selected and refined. Cubes were printed and subjected to tensile testing to characterize their material properties. Self-oscillating vocal fold models were then printed, coated with a thin layer of silicone representing the epithelium, and used in phonation tests to gather onset pressure, frequency, and amplitude data. RESULTS: The cubes were found to be anisotropic, exhibiting different modulus values depending on the orientation of the printed layers. The VF models self-oscillated and withstood the strains induced by phonation. Print parameters were found to affect model vibration frequency and onset pressure. Primarily due to the design of the VF models, their onset pressures were higher than what is found in human VFs. However, their frequencies were within a comparable range. CONCLUSION: The results demonstrate the ability to 3D print synthetic, self-oscillating VF models. It is anticipated that this method will be further refined and used in future studies exploring flow-induced vibratory characteristics of phonation.